EFL POSTGRADUATE STUDENTS’ ADOPTION AND PERCEPTIONS OF CHATBOT-ASSISTED ACADEMIC WRITING: - - Rahmayanti, Septi; Ivone, Francisca Maria; Tresnadewi, Sintha; Nomnian, Singhanat (JEES (Journal of English Educators Society), 2025)
Recently, chatbots have undoubtedly become valuable tools for foreign language learning, particularly in the context of academic writing. They influence the writing process, writing output, and language acquisition; however, their use also raises significant ethical and pedagogical concerns. This qualitative study employs the Technology Acceptance Model (TAM) framework to investigate the adoption andperceptions of chatbot-assisted academic writing among English as a Foreign Language (EFL) learners. Data were collected from 25 EFL learners enrolled in an English Language Education (ELE) postgraduate program through surveys and interviews. The study examines the use of chatbots across all phases of academic writing and explores the characteristics that contribute to their efficacy. The data was analyzed following the three stages of qualitative analysis by Miles et al. (2014), i.e., data condensation, data display, and drawing and verifying conclusions. Specifically, the study examines EFL learners' adoption and perceptions of chatbot - assisted writing based on perceived ease of use, perceived usefulness, attitudes toward usage, intention to use, actual use, and external variables. By investigating the experiences and attitudes of postgraduate EFL learners, the study aims to provide insights into the extent to which chatbots facilitate or potentially hinder the development of academic writing skills. The findings indicate that postgraduate students generally hold positive perceptions of chatbots, considering them useful tools for enhancing writing quality and efficiency. Future research could explore the long-term effects of chatbot- assisted writing and the complexities of studentengagement and interaction with chatbot technology in various academic writing contexts.HIGHLIGHTS: Positive Adoption of Chatbots in Academic Writing: Postgraduate EFL students generally perceive chatbots as useful, accessible, and efficient tools that help them improve the quality, organization, and speed of their academic writing, especially during planning, drafting, revising, and editing stages. Challenges and Ethical Concerns Remain: Despite the benefits, students show caution regarding overreliance on chatbots, particularly for formatting, citing, and referencing, due to concerns about accuracy, reliability, and maintaining academic integrity. Technology Acceptance Model (TAM) Validation: The study confirms that perceived ease of use, perceived usefulness, positive attitudes, and intention to use are strong factors driving chatbot adoption, supporting the applicability of the TAM framework in EFL academic writing contexts.